2008
DOI: 10.1089/scd.2007.0210
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Multipotent Human Keloid-Derived Mesenchymal-Like Stem Cells

Abstract: In this study, we report the isolation and characterization of a population of multipotent keloid-derived mesenchymal-like stem cells (KMLSCs) from keloid scalp tissues. These KMLSCs expressed the typical mesenchymal stem cell marker proteins CD13, CD29, CD44, CD90, fibronectin, and vimentin when they were cultured in serum-containing medium and when subsequent exposure to various differentiation media resulted in their differentiation into adipocytes, osteoblasts, chondrocytes, smooth muscle cells, and angiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 36 publications
2
71
0
1
Order By: Relevance
“…Keloid fibroblasts also exhibited a significantly increased proliferative and anti-apoptotic ability compared to normal skin fibroblasts (22). It was suggested that the keloid fibroblast may be a pluripotent precursor cell with multiple differentiation capacities, similar to the human skin precursor cell, and may be able to differentiate into several types of cells, such as adipocytes, osteoblasts, chondrocytes, smooth muscle cells, vascular endothelial cells, glial cells and oligodendrocytes under different culture conditions (23). Studies using gene chip technology demonstrated an upregulation of ~15% of the genes in keloid fibroblasts, among which the most important are proinflammatory factors, such as interleukin (IL)-1α, IL-1β, IL-6 and tumor necrosis factor-α (TNF-α) (24,25).…”
Section: Keloid Fibroblast Abnormalities May Be the Main Cause Of Kelmentioning
confidence: 99%
“…Keloid fibroblasts also exhibited a significantly increased proliferative and anti-apoptotic ability compared to normal skin fibroblasts (22). It was suggested that the keloid fibroblast may be a pluripotent precursor cell with multiple differentiation capacities, similar to the human skin precursor cell, and may be able to differentiate into several types of cells, such as adipocytes, osteoblasts, chondrocytes, smooth muscle cells, vascular endothelial cells, glial cells and oligodendrocytes under different culture conditions (23). Studies using gene chip technology demonstrated an upregulation of ~15% of the genes in keloid fibroblasts, among which the most important are proinflammatory factors, such as interleukin (IL)-1α, IL-1β, IL-6 and tumor necrosis factor-α (TNF-α) (24,25).…”
Section: Keloid Fibroblast Abnormalities May Be the Main Cause Of Kelmentioning
confidence: 99%
“…1-2 cm 2 pieces of human skin were washed with HBSS, cut into 4-to 6-mm pieces, washed again, and incubated in Dispase (Invitrogen) overnight at 4 o C as previously described Moon et al, 2008). Briefly, the epidermis was manually removed from each tissue piece, and the dermis was cut into small pieces and incubated in Collagenase type IV (Invitrogen) for 30-60 min at 37 o C. Then samples were centrifuged at 1,000 rpm for 5 min.…”
Section: Preparation Of Human Labia Minora Dermis-derived Fibroblastsmentioning
confidence: 99%
“…The strained cell suspension was centrifuged and resuspended with GM. Harvested cells were seeded at a density of 1 × 10 5 cells/cm 2 on a 10-cm 2 tissue culture plate (BD Bioscience) and incubated at 37 o C with 5% CO2 Moon et al, 2008). The cells were passaged by removing the medium and incubating the cells with 0.05% trypsin/EDTA containing 1 mM EDTA for 3 min at 37 o C. The cells were passaged every 3 days.…”
Section: Preparation Of Human Labia Minora Dermis-derived Fibroblastsmentioning
confidence: 99%
“…12) The current study successfully isolated, characterized and verified the differentiation potential of human SB cells. 13) In case of UCB, there are some limitations in collecting and supplying the demand for tissue, so there could be a limitation in its clinical application. Also the tissue being allogenic to the receiver may raise some issues regarding its compatibility.…”
Section: 4-7)mentioning
confidence: 99%